Acute Pancreatitis with Splenic Infarction as Early Postoperative Complication following Laparoscopic Sleeve Gastrectomy - Aleksandr Kalabin; Vishnu R. Mani; Ankita Mishra; Hector Depaz; Leaque Ahmed (Case Reports in Surgery)
Obesity is becoming a global health burden along with its comorbidities. It imposes tremendous financial burden and health costs worldwide. Surgery has emerged as the definitive treatment option for morbidly obese patients with comorbidities. Laparoscopic sleeve gastrectomy is performed now more than ever making it imperative for physicians and surgeons to recognize both the common and the uncommon risks and complications associated with it. In this report we describe a rare early life-threatening postoperative complication following laparoscopic sleeve gastrectomy. From our extensive review of literature, there is no existing report of acute pancreatitis with splenic infarction postsleeve gastrectomy to this date.